Two new species and a new record of Epidendrum (Orchidaceae: Laeliinae) from Costa Rica - Pupulin, Franco (2010)
Two new species of Epidendrum are described and illustrated from Costa Rica. Epidendrum fulfordianum is compared with E. chlorocorymbos, from which it can be distinguished by the much larger flowers, the wider petals and entire, subrectangular, retuse-mucronate midlobe of the lip. Similar to E. barbeyanum, the smaller E. pseudobarbeyanum can be easily distinguished by the short and straight, few-leaved stems, the few-flowered inflorescence, and the distinctly smaller flowers. A third species, Epidendrum villotae, is recorded and illustrated on the basis of a Costa Rican specimen.